Influence of Maleic anhydride on mechanical properties and morphology of Hydroxyapatite/Poly-(lactic acid) composites - Nainar, S.M.; Begum, S.; Hasan, Z.; Ansari, M.N.M.; Anuar, Hazleen (TESMA, 2012)
In this study, the effect of Maleic anhydride on mechanical properties such as tensile strength, flexural strength and modulus of Hydroxyapatite (HA)/Polylactic Acid (PLA) composites were determined. Maleic-anhydride (MAH)-grafted- PLA was filled with Hydroxyapetite (HA) using Haake Rheocorder mixer. The composite mixture was then moulded to form the required tensile and flexural test specimens using Injection Moulding process. The composites with Maleic anhydride (MAH) content of 0wt%, 0.5wt%, 1.0wt% and 2.0wt% were fabricated. Tensile tests according to ASTM-D 638 standards were conducted. Flexural tests according to ASTM-D 790 standards were conducted. The results showed that addition of maleic anhydride (MAH) has improved the mechanical properties. Other properties such as stiffness and yield point, were also evaluated from the results of tensile tests.